Social abilities to interact in virtual learning environments - da Silva, Edilaine Cristina; Corradi-Websterz, Clarissa Mendonça (Investigación y Educación en Enfermería, 2011)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To investigate the association between social abilities characteristics needed to interact academically and the use of communication tools of a virtual learning platform. Methodology. Quantitative study, performed in Ribeirão Preto, São Paulo, Brazil, in 2006. 32 nursing students from the on line class about humor and personality disorders and some from the psychiatric nursing class participated. The virtual learning platform used for the on line class was TELEDUC. Instruments: communication tool access registration, social characteristics to interact with their colleagues in the academic environment questionnaire. Correlation tests were performed between the scores of the social abilities characteristics, and the frequency the virtual environment communication tools were used (Pearson correlation). Results. A moderate positive correlation was found between the sociability factor and access to the “Chat” (r=0.61) and “Forum” (r=0.50) tools; Moderate negative correlation between the levels of aggression and the “mail” tool “ (r=-0.37); Positive correlation between the levels of leadership and “mail” (r=0.53); moderate negative correlation between inhibition levels and the “Chat” (r=-0.65) and “Forum” (r =-0.63) tools. Conclusion. Social abilities contribute to the participation of the students in long distance educational processes, so it needs to be taken into account in the teaching- learning virtual environments.